Organic amendments, deficit irrigation, and microbial communities impact extracellular polysaccharide content in agricultural soils. (November 2021) - Hale, Lauren; Curtis, Daniel; Leon, Nicole; McGiffen, Milton; Wang, Dong
Abstract: Soil extracellular polysaccharides (EPSac) can improve irrigation water productivity in agriculture by increasing soil aggregate stability and retaining water on and around plant roots. However, limited studies assay soil EPSac directly from field trials and to date no studies have examined the long-term confounding impacts of organic amendments and deficit irrigation on soil EPSac and the underlying microbial communities. We quantified soil aggregate stability, EPSac content, chemical properties, and microbial community compositions and abundances in separate field studies in turfgrass and tomato. Soil samples were collected 4–5 years after soil amendment with compost, biochar, their combination, or biosolids from plots that had received full and deficit irrigation regimens for 4 years. Amending the soil with compost, with or without biochar co-application, enhanced soil total carbon, aggregate stability, EPSac, and total soil microbial biomass and shifted microbial community structures, trends which were more pronounced under turfgrass than for tomato. In both sites deficit irrigation treatments had higher quantities of soil EPSac per unit of microbial biomass. Indicators of microbial physiological stress and ubiquitous classes of soil bacteria were associated with soil EPSac production. These results provide mechanistic understanding of organic amendment benefits in drought-impacted and deficit-irrigated agriculture. Graphical abstract: Image 1 Highlights: In a perennial system composts improved soil properties related to water productivity. Comparatively in an annual system there were fewer benefits of composts or biochar. Deficit irrigation increased extracellular polysaccharide: microbial biomass ratios. Extracellular polysaccharides associated with ubiquitous soil bacterial taxa.